2020
DOI: 10.3390/polym12081729
|View full text |Cite
|
Sign up to set email alerts
|

Physically Crosslinked Hydrogels Based on Poly (Vinyl Alcohol) and Fish Gelatin for Wound Dressing Application: Fabrication and Characterization

Abstract: We developed the interpenetrating double network composite hydrogel based on poly (vinyl alcohol) (PVA) and fish gelatin (FG) via thermal treatment and repeated freeze-thawing. A function of salicylic acid was incorporated into the hydrogel to improve its antibacterial properties. The color values, water contents, water evaporation rate, and swelling behavior were investigated. The drug-loading performance of the composite hydrogel was demonstrated by loading salicylic acid in various hydrogel systems. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Due to their favorable bio-application properties, research on hydrogel materials based on gelatin and PVA blends is widely reported in the literature. The articles, in particular, are concerned with using these materials for a variety of medical purposes, including tissue engineering [ 41 , 58 , 59 , 60 , 61 , 62 ], wound dressings [ 62 , 63 , 64 , 65 , 66 ], drug delivery systems [ 62 , 67 ], implants [ 68 ], and vascular grafts [ 69 ]. However, other fields of application have also been intensively explored, such as heavy metal removal [ 70 ], biodegradable food packaging [ 40 ], and enzyme immobilization [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their favorable bio-application properties, research on hydrogel materials based on gelatin and PVA blends is widely reported in the literature. The articles, in particular, are concerned with using these materials for a variety of medical purposes, including tissue engineering [ 41 , 58 , 59 , 60 , 61 , 62 ], wound dressings [ 62 , 63 , 64 , 65 , 66 ], drug delivery systems [ 62 , 67 ], implants [ 68 ], and vascular grafts [ 69 ]. However, other fields of application have also been intensively explored, such as heavy metal removal [ 70 ], biodegradable food packaging [ 40 ], and enzyme immobilization [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that, in each case, the properties of gelatin/PVA hydrogels depend not only on the ratio of these components but also on the cross-linking method used and the final form/shape of the received material. These hydrogels can be produced with a variety of cross-linking methods based on using chemical agents (e.g., glutaraldehyde [ 41 , 59 ], sodium trimetaphosphate [ 69 ], genipin [ 60 ], and microbial transglutaminase [ 58 ]) or physical processes, such as irradiation [ 61 , 63 ] and repeated freeze-thaw cycles [ 58 , 59 , 64 , 65 , 68 ]. Furthermore, they can be obtained in the form of thin films [ 58 , 63 , 64 , 66 , 69 ], membranes [ 67 ], and three-dimensional porous constructs [ 41 , 59 , 60 , 61 , 65 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salicylic acid was added to the hydrogel to exert antibacterial properties; it showed good sustained release properties verified by activity tests. These results demonstrated that PVA-fish gelatin based interpenetrating hydrogel is an appropriate biomaterial for drug-carrying wound dressing application [ 121 ]. In a similar study, a 3D-hydrogel patches were printed using fish gelatin and used for the local delivery of PEGylated liposomal doxorubicin.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…In the present work, sodium alginate and fish gelatin were employed to develop interpenetrating double network gels. Gelatin‐based hydrogels have been applied successfully for regenerative medicine, wound dressings, and drug delivery 20–22 . There are many animal sources of gelatins such as pig, cattle, and fish.…”
Section: Introductionmentioning
confidence: 99%